PENINGKATAN KEMAMPUAN MEMBACA SISWA DALAM MEMAHAMI RECOUNT TEKS MENGGUNAKAN TEKNIK “SUMMARIZING” PADA SISWA KELAS X - 7 SMA NEGERI 17 SURABAYA: SMA NEGERI 17 SURABAYA - FIANICO SUKMANA ROZY INTAN MAULIDA QORRY, AINA (Dewan Pendidikan Bondowoso, 2021)
English proficiency is a necessity and necessity in the current era of communication and globalization, however, the existing learning still produces scores below the Minimum Completeness Criteria (KKM). This phenomenon occurs because the student learning process is very passive. So that the emergence of a feeling of insecurity in students. To overcome this problem, a learning innovation is needed so that student learning outcomes are better. Building a more meaningful learning atmosphere by making students more involved is a learning innovation that continues to be developed. One way to build a meaningful learning atmosphere is to use the